OPERATIONAL RISK ASSESSMENT SHIP CONSTRUCTION CAUSES MATERIAL IMPORT USING HOUSE OF RISK (HOR) AND CRITICAL CHAIN PROJECT MANAGEMENT: CASE STUDY IN GRESIK SHIPYARD INDUSTRY - Basuki, Minto; Hildawan Mahendra, Oka (Journal of Marine-Earth Science and Technology, 2021)
This research is aimed to conduct risks assessment of ship building process in the part of materials procurement especially imported materials. The problem in Gresik shipyard industry is late material import, which impact the project delay. This research used House of Risk (HOR) combination and Critical Chain Project Management (CCPM) method analysis. Data analysis was obtained from data sample on new construction work of 2 x 1200 HP tug-boat at the Gresik Shipyard. The data used was related with materials procurement especially imported materials. The analysis used House of Risk (HOR) method and obtained 14 risk events which occurred in planning process and imported components for tug-boat 2x1200HP construction and 22 events as risk agent. There were 14 highest risks needing risk mitigation to reduce the impact. Rescheduling result of the material arrival and imported component used Critical Chain Project Management (CCPM) method. It was able to save time duration from activities schedule of 50%; previous schedule was 84 days become 42 days.